2020
DOI: 10.2174/1574887115666200421110107
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Proctosoll Allevia in the Management of Haemorrhoidal Disease in Adults: A Prospective Randomized Clinical Trial

Abstract: Introduction: Hemorrhoidal Disease (HD) is a very common anorectal disorder that affects millions of people around the world and represents a major medical and socioeconomic problem. The aim of the present study was to assess the safety and efficacy of Proctosoll Allevia® in patients affected by symptomatic HD in comparison with the results obtained from a control group. Material and Methods: From Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…It has been involved in several processes as tissue regeneration and matrix organization. It has been observed that local administration is effective helping wounds healing due to the barrier effect protecting the injured epithelium [16,17] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been involved in several processes as tissue regeneration and matrix organization. It has been observed that local administration is effective helping wounds healing due to the barrier effect protecting the injured epithelium [16,17] .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, non-surgical treatments such as topical and pharmacological approaches have not been fully effective. Treatment with Proctosoll Allevia ® was proven effective against I–II degree symptomatic hemorrhoids with a good profile of tolerability and safety ( 42 ). A clinical study by our group suggested that treatment with Anoac-H polyherbal formulation exhibited efficacy and safety in patients with bleeding hemorrhoids ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Foram avaliados 45 indivíduos distribuídos em grupo 1 (tratado com Proctosoll Allevia® + dieta controlada) e grupo 2 (sem tratamento + dieta controlada). Aqueles tratados com o extrato apresentaram melhora dos sintomas num período 14 dias antes do grupo controle (Sturiale et al, 2020).…”
Section: Estudos Clínicos Randomizados Com Fitoterápicosunclassified